Assessment of the emotional intelligence and its dimensions of students at beginning of their medical profession education - Singh, Harmesh; Singh, Ishneet; Soni, R. K. (International Journal of Contemporary Pediatrics, 2022)
Background: Medicine involves not only prescriptions but also a well-developed emotional intelligence (EI). The assessment of EI of students at their entry to medical professional training may identify weaknesses, if any, so as to be taken care during the course. Thus, it may be relevant to explore it and its dimensions because it is still a nascent field of research, hence this study was planned. Methods: Objectives were to assess the EI and its dimensions of first year MBBS students. Study design was a descriptive and cross-sectional study. Study sample were 150 first year MBBS students. Ethical approval from institutional ethics committee and informed written consent from participants obtained; administered a questionnaire based EI test. Data obtained was analysed by ANOVA. Results: The 53.1 % participants were females and 46.9% males. The 73.1% were 17-18 years of age and 26.9% were 19-21 years old. The mean total EI score was 353.01. Among the emotional dimensions sensitivity was significantly low (p=0.047) in males (87.35±15.34) than females (92.49±9.071). The emotional competency was significantly low (p=0.055) in the elder group (153.59±26.99) than the younger one (160.61±15.762). Conclusions: The study identified certain gender and age differences in the EI and some weaknesses among first year medical students. Emotional sensitivity was significantly low in males and emotional competency was significantly low in the elder age group.